Power and influence of information technology project teams : an empirical study in a South African context - Kobedi, Mpho David (My University, 2017)
Information systems development (ISD) project teams are involved in requirements elicitation, analysis, development, testing and deployment of various information technology solutions. These teams often compete with each other for limited resources in an attempt to fulfil their organisational mandate. As a result, project teams can exert power over each other and employ various influence tactics in attempt to gain and maintain positions of power which allow them to control key resources and influence decision making processes. This study examined the strategic environmental and structural conditions of fulfilment which influence the power of ISD project teams, and the extent to which influence tactics can impact on team power level. Data was collected using a structured questionnaire instrument. A sample of 106 teams from five companies was obtained. The companies operate in the financial services and government sectors. A single key informant responded on behalf of their team. Correlation and regression analysis was used to test the hypothesized links between power and the structural conditions of fulfilment namely centrality and substitutability, as well as, the environmental condition of coping with uncertainty. The moderating effects of influence tactics on these relationships was tested via hierarchical moderated regression. Results indicated that the strategic condition of coping with uncertainty significantly and positively affects perceived team power, whilst substitutability significantly and negatively affects perceived team power. Support for the structural condition of centrality was not found to be significant. Additionally, the influence tactic of rational persuasion was found to moderate the relationship between power and coping with uncertainty such that rational persuasion interacts with coping with uncertainty to affect power. Results also indicated that the influence tactic of collaboration was not a moderator but rather has significant direct effects on perceived team power. The study concluded that ISD project teams who cope with project uncertainties and whose tasks and functionalities are difficult to replace, as well as, those who effectively collaborate with other teams will have greater power within project settings. Moreover, ISD project teams can combine rational persuasion tactics with coping with uncertainty to exert even stronger effects on power. The outcomes of this study help to bring an understanding of the impact of the strategic conditions factors on perceived team power within ISD project settings, as well as the role of specific influence tactics in the formation of power.
Submitted in partial fulfilment of the requirements for the degree of Masters of Commerce (M Com) at the University of the Witwatersrand, February 2017
Keywords: Management information systems; Teams in the workplace